Effective modern C++ 42 specific ways to improve your use of C++11 and C++14 - Meyers, Scott (O'Reilly Media, 2015)
Coming to grips with C++11 and C++14 is more than a matter of familiarizing yourself with the features they introduce (e.g., auto type declarations, move semantics, lambda expressions, and concurrency support). That's where this practical book comes in. It describes how to write truly great software using C++11 and C++14 -- i.e. using modern C++ ... Effective Modern C++ follows the proven guideline-based, example-driven format of Scott Meyers' earlier books, but covers entirely new material.